2014
DOI: 10.14710/jitaa.39.2.111-116
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of Protein Metabolism in Goats Fed Diets With Different Portion of Sugarcane Bagasse

Abstract: ABSTRAKLimabelas ekor kambing Jawarandu jantan digunakan untuk mengkaji pengaruh porsi ampas tebu dalam pakan terhadap beberapa parameter metabolisme protein. Ternak memiliki rerata bobot badan sebesar 18 kg dengan rerata umur 18 bulan. Ternak ditempatkan pada kandang metabolisme dan dialokasikan sesuai rancangan acak lengkap yang menerima tiga jenis pakan perlakuan, dengan porsi ampas tebu sebesar 15, 25, dan 35%. Setelah delapan minggu masa adaptasi terhadap pakan dan lingkungan perlakuan, setiap kelompok pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…As shown in Table 4, the purine derivatives were not significantly different among the four treatments. Ariyani et al (2016) found that purine derivatives were not significantly different (P > 0.05) when using bagasse as basal feed. Purine derivatives reflect that the use of FCC does not interfere with the digestive system in cattle.…”
Section: Resultsmentioning
confidence: 80%
“…As shown in Table 4, the purine derivatives were not significantly different among the four treatments. Ariyani et al (2016) found that purine derivatives were not significantly different (P > 0.05) when using bagasse as basal feed. Purine derivatives reflect that the use of FCC does not interfere with the digestive system in cattle.…”
Section: Resultsmentioning
confidence: 80%
“…Sugarcane bagasse is one of agricultural wastes that frequently used to sustain roughage availability for ruminant throughout the year. Previously, the maximum level of sugarcane bagasse in TMR for goat was determined to be 25% (Ariyani et al, 2014). By synchronizing ruminal releases of energy and protein, the use of sugarcane bagasse in diet is expected to be more efficient.…”
Section: Resultsmentioning
confidence: 99%
“…The portion of sugarcane bagasse in TMR was the highest among ingredient feedstuffs (Table 2). Most fiber components of sugarcane bagasse are tightly bound to lignin as lignohemicelluloses and lignocelluloses (Ariyani et al, 2014;Ramli et al, 2005).…”
Section: Discussion Sugarcane Bagasse Based Tmr With Different Synchronization Indexmentioning
confidence: 99%